Measuring the accessibility deprivation of concentrated resettlement communities in China: An integrated approach of space syntax and multi-criteria decision analysis. (January 2023) - Yang, Chen; Qian, Zhu; Li, Huan
Abstract: China's rapid urbanization involves the large-scale relocation of rural villagers and the production of concentrated resettlement communities in urban areas. This new urban population's post-resettlement adaptation and socio-economic situations raise concerns for urban scholars and policymakers alike. This paper invokes the concept of deprivation and aims to establish indices of multiple deprivations (IMDs) for such communities. In doing so, this research use accessibility as a proxy and integrates the space syntax approach with multi-criteria decision analysis to construct the IMDs of concentrated resettlement communities in Hangzhou, China. The findings suggest that material deprivation may not be the primary concern for residential segregation of resettlement communities in urban areas. Besides, the accessibility to different services reflects diverse deprivation patterns among resettlement communities. Moreover, various stakeholder groups' perceptions of deprivation may lead to different results of the IMDs. The diverse criteria or domains of deprivation contribute differently to the deprivation, which requires a tailored treatment strategy when constructing IMDs, such as the sensitivity analysis used in this research. The proposed measurement of deprivation has important policy implications for sustainable urban development in China. Highlights: The indices of multiple deprivations (IMDs) of resettlement communities are proposed. Material deprivation is not the primary concern for the residential segregation of resettlement communities. The accessibility to different services reflects diverse deprivation patterns. Various stakeholder groups' perceptions of deprivation may lead to different results of IMDs.